Coexistent squamous cell carcinoma and adenoid basal carcinoma in the uterine cervix and infection with human papillomavirus (HPV 31) - Yu-Chieh Lin; Cherng-Lih Perng; Yi-Ming Chang; Yao-Feng Li; Yuan-Ming Tsai; Gwo-Jang Wu; Chih-Kung Lin (Elsevier, 2013)
Objective: Adenoid basal carcinoma (ABC) is an uncommon neoplasm of the uterine cervix. ABC can be accompanied by carcinoma in situ or invasive carcinoma. Most cases are discovered accidentally during radical hysterectomy. ABC is associated with a high risk of human papillomavirus infection (HPV), most often HPV 16 infection. Case report: We present a rare case of an 86-year-old Taiwanese married woman who suffered from bloody vaginal discharge and occasional lower abdominal pain and received cervical biopsy. The pathological report revealed squamous cell carcinoma (SCC) of the uterine cervix. After radical hysterectomy, bilateral salpingo-oophorectomy, and bilateral pelvic and para-aortic lymph node dissection, the final pathological report revealed SCC coexisting with ABC, and both of the components were infected by HPV 31. After receiving radiotherapy, she maintained outpatient department follow-up. Conclusion: A literature review revealed that this was a rare case of combined ABC-SCC associated with HPV 31 infection. In this case, the ABC component did not affect the tumor stage because it was confined to the cervix. However, we must avoid overestimating the clinical stage because the ABC component is thought to be a benign lesion.